Relationship between BMI and three different devices used in urinary incontinence procedures and anatomical structures in fresh cadavers. A pilot study. (November 2015) - Haddad, Jorge Milhem; Fiorelli, Lilian Renata; de Lima Takami, Tatiane; Peterson, Thais Villela; Soares-Jr, José Maria; Baracat, Edmund C.
Abstract: Objective: To demonstrate the needle positioning during three types of slings in relation to anatomical structures in fresh cadavers and to evaluate if this positioning is influenced by body mass index (BMI). Methods: TVTr sling (retropubic), TVT-O sling (transobturator) and mini-sling (TVT-Secur™) were performed in ten fresh cadavers, followed by dissection of the pudendal (genital) area (external evaluation) and abdominal cavity (internal evaluation). The distance between the devices used in each technique and specific anatomical structures (vessels and bowel) was measured. Results: The mean distance between TVTr needles and the closest segment of the bowel was 5.0 ± 1.1 cm. The mean distance between the TVTr needles and iliac vessels was 8.55 ± 1.59 cm, and this distance was inversely proportional to BMI. However, the both correlations were not significantly ( p  < 0.05). The mean distance from TVT-O needle to obturator vessels and nerve was 2.25 ± 0.34 cm. This distance was inversely proportional to BMI, but it was not statistically significant. Conclusion: Our data suggested that BMI may be not an important factor for influencing the relationship between the devices and anatomical structures in three different slings in fresh cadavers.